Bioactive Compound Profiling of Olive Fruit: The Contribution of Genotype - Soraya Mousavi; Vitale Stanzione; Roberto Mariotti; Valerio Mastio; Aristotelis Azariadis; Valentina Passeri; Maria Cristina Valeri; Luciana Baldoni; Marina Bufacchi (MDPI AG, 2022)
The health, therapeutic, and organoleptic characteristics of olive oil depend on functional bioactive compounds, such as phenols, tocopherols, squalene, and sterols. Genotype plays a key role in the diversity and concentration of secondary compounds peculiar to olive. In this study, the most important bioactive compounds of olive fruit were studied in numerous international olive cultivars during two consecutive seasons. A large variability was measured for each studied metabolite in all 61 olive cultivars. Total phenol content varied on a scale of 1-10 (3831-39,252 mg kg−1) in the studied cultivars. Squalene values fluctuated over an even wider range (1-15), with values of 274 to 4351 mg kg−1. Total sterols ranged from 119 to 969 mg kg−1, and total tocopherols varied from 135 to 579 mg kg−1 in fruit pulp. In the present study, the linkage among the most important quality traits highlighted the scarcity of cultivars with high content of at least three traits together. This work provided sound information on the fruit metabolite profile of a wide range of cultivars, which will facilitate the studies on the genomic regulation of plant metabolites and development of new olive genotypes through genomics-assisted breeding.